A 7300-yr-old environmental history of seabird, human, and volcano impacts on Carlisle Island (the Islands of Four Mountains, eastern Aleutians, Alaska). Issue 3 (11th January 2019) - Kuzmicheva, Evgeniya A.; Smyshlyaeva, Olesya I.; Vasyukov, Dmitry D.; Khasanov, Bulat F.; Krylovich, Olga A.; Okuno, Mitsuru; West, Dixie L.; Hatfield, Virginia L.; Savinetsky, Arkady B.
Abstract: We present the results of multiproxy study of a peat deposit from Carlisle Island (the Islands of Four Mountains, Aleutians). Vegetation on the initial stage of the peat is characterized by heath vegetation dominated by Ericales indicating cold conditions at 7300–6100 cal yr BP. The appearance of Betula and Alnus is the result of long-distance transportation attributable to strong winds at this time. Sedge-grass (Cyperaceae and Poaceae) communities began replacing heath vegetation at 6100 cal yr BP because of the climatic amelioration. C/N ratios and pollen spectra remain relatively stable at 6100–2450 cal yr BP. For the CR-03 peatland, volcanic tephra contributed significantly to the Fourier transform infrared spectroscopy spectral data. Volcanic input created overlap of an aluminosilicate signal with carbohydrate vibrations. Significant changes occurred at approximately 2450 cal yr BP when there is the some evidence of cooler and wetter conditions of the Neoglacial. High values of δ 15 N observed at 7100–7000 cal yr BP reflect the fertilizing effect of seabird nesting colonies. A decrease in δ 15 N ca. 6900 cal yr BP may indicate initial settlement on Carlisle Island corresponding with harvesting seabirds. Human predation continued until a series of volcanic eruptions, which deposited Okmok II and CR-02 tephra layers at ca. 2000 and 1050 cal yr BP, respectively.